2019
DOI: 10.1007/s00401-019-02064-2
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Ketogenic diet ameliorates axonal defects and promotes myelination in Pelizaeus–Merzbacher disease

Abstract: The original article was published with an erroneously duplicated image in Fig. 2a. The corrected Fig. 2a is given in the next page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Brain hemispheres were embedded in paraffin, sectioned coronally, and labeled chromogenic for CD3, GFAP, APP, and MAC3 and with fluorescent antibodies for CAII, Olig2, and PDGFRa as essentially described in refs. 78 , 79 . TUNEL staining of paraffin fimbria sections for quantification of apoptotic cells was performed according to the manufacturer’s protocols (DeadEnd™ Colorimetric TUNEL System, Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Brain hemispheres were embedded in paraffin, sectioned coronally, and labeled chromogenic for CD3, GFAP, APP, and MAC3 and with fluorescent antibodies for CAII, Olig2, and PDGFRa as essentially described in refs. 78 , 79 . TUNEL staining of paraffin fimbria sections for quantification of apoptotic cells was performed according to the manufacturer’s protocols (DeadEnd™ Colorimetric TUNEL System, Promega).…”
Section: Methodsmentioning
confidence: 99%
“…This study explored the relevant mechanism of short-term KD treatment in SCI rats [ 37 ]. Additionally, studies have found that HDLc showed small increases after ketogenic phases, but there was no significant change over 12 months [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary cholesterol supplementation does not cure PMD but rather helps relieve the oligodendrocytes from the cytoplasmic accumulation of PLP1 [ 133 ]. The ketogenic diet, which is high in fat and low in carbohydrates, helps to restore the oligodendrocytes, thus improving myelination in +PlpTg 72/72 mice due to the ketone bodies that can cross the blood–brain barrier and that enhance lipid synthesis [ 134 ].…”
Section: Therapiesmentioning
confidence: 99%